TRANSLATION FEATURES OF ENGLISH AND UZBEK NEWSPAPER HEADLINES - Eshboyev, Abdushukur Berdinazarovich (Educational Research in Universal Sciences, 2023)
This article examines the translation features of English and Uzbek newspaper headlines. Newspaper headlines play a crucial role in capturing readers’ attention and conveying the main ideas of news articles. The study focuses on identifying and analyzing the linguistic and cultural aspects involved in translating headlines from English into Uzbek and vice versa. It explores the strategies employed by translators to ensure the effectiveness and communicative impact of headlines in the target language. Additionally, the article investigates the challenges encountered in the translation process, such as maintaining conciseness, capturing cultural nuances, and preserving the journalistic style. By examining a corpus of newspaper headlines, this research aims to provide insights into the translation practices specific to this genre and contribute to the field of translation studies.